Pengaruh Budaya Organisasi Dan Lingkungan Kerja Yang Berkelanjutan Terhadap Kepuasan Kerja Karyawan PT. Grahaprima Suksesmandiri Tbk. (GrahaTrans) - Nurkhaliza, Fitri; Lestari , Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
One of the indicators that support Human Resource Management is the level of employee job satisfaction. There are many factors that can influence employee job satisfaction, including organizational culture and a sustainable work environment. This study aims to analyze the influence of organizational culture (X1) and a sustainable work environment (X2) on employee job satisfaction (Y) at PT Grahaprima Suksesmandiri Tbk (GrahaTrans). This research uses a quantitative approach with a causal associative research design. The data collection technique was carried out by distributing questionnaires to eighty-six respondents, and data analysis was conducted using IBM Statistical Package for the Social Sciences (SPSS) version 23. The results of the study show that organizational culture has a positive and significant effect on employee job satisfaction with a t-value of 3.987 and a significance level of 0.000. A sustainable work environment also has a positive and significant effect on job satisfaction with a t-value of 4.161 and a significance level of 0.000. Simultaneously, both of these variables have a significant influence on employee job satisfaction with an F-value of 51.181 and a significance level of 0.000. These findings indicate that improving organizational culture and creating a healthy and sustainable work environment are very important to increase overall employee job satisfaction.